The No Child Left Behind legislation : educational research and federal funding - Carlson, Jerry S.; Levin, Joel R. (Emerald Publishing Limited : Information Age Pub., 2005)
With the publication of this book, the scholarly journal Issues in Education: Contributions from Educational Psychology is moving to a book series publication format. Carlson (University of California-Riverside) and Levin (University of Arizona) present material on aspects of the No Child Left Behind legislation.
Keywords: United States. -- No Child Left Behind Act of 2001.; Education -- Research -- United States.; Education and state -- United States.; Education -- Research -- United States -- Finance.; Education -- Educational Policy & Reform -- Federal Legislation.; Educational strategies and policy.; Central, national, federal government policies.; elektronické knihy; electronic books